2021
DOI: 10.5708/ejmh.16.2021.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Mental Health Literacy : Adaptation and Validation of the Portuguese Version of the Mental Health Literacy Scale (MHLS)

Abstract: Understanding mental health literacy is essential for promoting empowerment and proactivity in patients, reducing stigma, and increasing population awareness. The constitutive dimensions of mental health literacy are still being researched, and instruments’ research can shed light on the involved processes. The Mental Health Literacy Scale (MHLS) is a self-report measure of mental health literacy. This study aimed to adapt the MHLS to Portuguese and evaluate mental health literacy in a broad sample. A broad sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
6
10
0
Order By: Relevance
“…14,31,33 Therefore, patients that have a higher level of mental health literacy and a more positive attitude regarding seeking professional help are the ones that do it the most. 30,36 Therefore, patients that are already followed in regular appointments because of their psychiatric problems, such as those who participated in the present study, probably know that they cannot solve the problems by themselves and that they need the help of healthcare professionals. As the appointments are in public institutions and Portugal has a high governmental financial participation in healthcare costs, it seems less likely that low HSB is associated with financial problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,31,33 Therefore, patients that have a higher level of mental health literacy and a more positive attitude regarding seeking professional help are the ones that do it the most. 30,36 Therefore, patients that are already followed in regular appointments because of their psychiatric problems, such as those who participated in the present study, probably know that they cannot solve the problems by themselves and that they need the help of healthcare professionals. As the appointments are in public institutions and Portugal has a high governmental financial participation in healthcare costs, it seems less likely that low HSB is associated with financial problems.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 It has also been shown that seeking help one time changes the way each patient perceives help-seeking behavior. 31 The high representativeness of women in the sample may also contribute to the lack of association between stigma and HSB, as women reveal less stigma-related barriers to help-seeking 10 and higher mental health literacy, 36 both of which may promote adjusted help-seeking behaviors. There is also high representativeness of graduates and post-graduates in the sample and education is associated with reduced stigma and high levels of mental health literacy, 10 namely a high level of knowledge about mental health, awareness, and health-seeking attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mental Health Literacy Scale (MHLS) [ 14 ] presents a three-factor structure (attitudes towards mental illness; knowledge about mental illness; and ability to recognize symptoms), which explains 35% of the total variance (a value lower than the MHKQ). On the other hand, the internal reliability of the factors tends to be better than in the MHKQ (ranging from 0.66 and 0.89).…”
Section: Discussionmentioning
confidence: 99%
“…Most assessment tools on mental health literacy usually focus on knowledge about mental disorders. For example, the Mental Health Literacy Scale [ 13 ], which was validated for the Portuguese population in 2021 [ 14 ], is entirely focused, for instance, on the recognition of mental disorders, knowledge of their risk factors and causes, knowledge of self-treatments, or knowledge of available professional help. However, the assessment tool Mental Health Knowledge Questionnaire (MHKQ) does not concretely focus on mental disorders.…”
Section: Introductionmentioning
confidence: 99%